A case of lupus cystitis - Kunimi, K (Hinyokika kiyo. Acta urologica Japonica, 1989)
A case of lupus cystitis in a 23-year-old male is reported. The patient began to complain of diarrhea and vomiting in October, 1985. When the diagnosis of systemic lupus erythematosus (SLE) was established at the Department of Internal Medicine in our hospital, he was referred to our clinic for examination of pollakisuria on November 22. DIP revealed a loss of bladder distensibility, and bilateral hydronephrosis and hydroureter. Transurethral cold cup biopsies revealed subcutaneous edema. A diagnosis of lupus cystitis was made and he was treated with steroids, which resulted in symptomatic and radiographic improvement